Chaotic Behaviour Investigation of a Front Opposed-Hemispherical Spiral-Grooved Air Bearing System - Cheng-Chi Wang (Shock and Vibration)
In recent years, spiral-grooved air bearing systems have attracted much attention and are especially useful in precision instruments and machines with spindles that rotate at high speed. Load support can be multidirectional and this type of bearing can also be very rigid. Studies show that some of the design problems encountered are dynamic and include critical speed, nonlinearity, gas film pressure, unbalanced rotors, and even poor design, all of which can result in the generation of chaotic aperiodic motion and instability under certain conditions. Such irregular motion on a large scale can cause severe damage to a machine or instrument. Therefore, understanding the conditions under which aperiodic behaviour and vibration arise is crucial for prevention. In this study, numerical analysis, including the Finite Difference and Differential Transformation Methods, is used to study these effects in detail in a front opposed-hemispherical spiral-grooved air bearing system. It was found that different rotor masses and bearing number could cause undesirable behaviour including periodic, subperiodic, quasi-periodic, and chaotic motion. The results obtained in this study can be used as a basis for future bearing system design and the prevention of instability.